LEXICAL CHANGE WITH REFERENCE TO SOCIAL CONTACT AMONG THE SPEAKERS OF PASE DIALECT - Rizka, Budi; Zainuddin, Zainuddin (English Department FBS UNP, 2016)
The aims of this study were to analyze the types, the patterns of lexical change with reference to social contact among the speakers of Pase dialect. The subjects of the study were personal documents written in Pase dialect as available in Language Department of Aceh. From the research, 505 lexicons were found, where 154 lexicons underwent loss. The percentage of lexical loss of noun was 75.32%, adjective 12.34%, and verb 12.34%. The number of lexical borrowings was 177 lexicons. The percentage of lexical borrowing of noun was 78.53%, adjective 15.25%, verb 5.09%, and adverb 1.13%. In phonological change, there were 155 lexicons. The percentage of phonological changes of noun was 89.68%, adjective 6.45%, verb 2.38%, and adverb 1.29%. In semantic change, there were 19 lexicons found, the percentages of which are: noun 68.42%, adjective 10.53%, and verb 21.05%. The patterns of lexical change with reference to social contact among the speakers of Pase dialect were potential loss in lexical loss, borrowings in the patterns of loan-words, loan-blend, loan-translation. The patterns of phonological change were lenition, fortition, vowel and syllable structure, syncope, apocope, and epenthesis. In semantic change, the patterns were narrowing, extension, figurative use, and pejoration.Keywords: lexical borrowing, Pase dialect, phonological change, semantic change